The Role of Agency and Institutional Theory in the Planning and Realization for Capital Expenditures - Syaiful Hifni (Jurnal Dinamika Akuntansi)
The capital expenditures are part of direct expenditure in the regional budget. The other elements of capital expenditures are: personnel expenditure, and spending on goods and services. Planning and realization for capital expenditure in the regional budget for each Government Regional Work Units is a part of policy regional financial management in fiscal decentralization policy which need be increased to achieve value significantly over time. Increasing in planning and realization of capital expenditures is directly related to the amount of capital expenditure element that strengthens physical infrastructure which would strengthen economic growth for social welfare, regional competitiveness for facilitation and liberalization a single market and production base in AEC era. This study examines the role of agency theory and institutional theory in relation with planning and realization of capital expenditures of 82 (Eighty Two) Government Work Units of 3 (Three) regional government, namely Banjarmasin City, Banjar District, and Tanah Laut District in South Kalimantan Province. This study contributes to the accounting literature to assess role of conceptual framework with agency theory and institutional theory. The result of study showed: there are differences in the implementation of capital expenditure to meet AEC pillars and social welfare purposes by increasing capital expenditure through the role of the agency theory, and institutional theory. Relationship of agency theory and institutional theory with social welfare and AEC with the amount of C Contingency coefficient 0,313 and Cramer Coefficient of Association 0.191 indicates there are Moderate correlation: substantial relationship and Small correlation; Lower relationship association.